A case study of depression disorder among registered patients of Hospital Sultanah Bahiyah, Kedah / Sharir Aizat Kamaruddin ... [et al.] - Kamaruddin, Sharir Aizat; Zahari, Nur Iwani; Abd Aziz, Khairul Naim; Roslani, Muhammad Akmal; Ahmad Helmi, Nurhana Athirah (Universiti Teknologi MARA, Perlis, 2020)
Depression is a common chronic disorder that affects individual functioning and contributes to the increasing number of suicide rates. At present, the analysis of depression cases is carried out on a global scale and the trend data in the local scale has been found to be baffling. By solving this problem, it would allow the government and non-governmental bodies to understand the distribution of depression cases in the state of Kedah. This study aims to investigate the distribution of depression cases in Hospital Sultanah Bahiyah, Kedah. The age, gender and ethnicity of depression patients referred to this hospital were classified as secondary data as the basis of this analysis. The epidemiologic data of depression applied for this analysis were collected from 2014 until 2017. This study found that older patients (age 40 years old and above) were suffering from the depression disorder more than the youths (ages below 40 years old) (p= 0.0007). Meanwhile, in terms of gender, the female patients were found to be diagnosed with the depression disorder higher than the male patients (p= 0.0134). It was also found that there was no equal distribution among the ethnicity groups (p=0.005). The findings of this research can be used as the baseline information for concerned parties to monitor and formulate strategies and policies. This can help to promote the good health and well-being for the Sustainable Development Goal 3 achievement.